Psychogenic cough. Issue 9 (September 1983) - Shuper, A; Mukamel, M; Mimouni, M; Lerman, M; Varsano, I
Abstract : Psychogenic cough is croupy and explosive, never occurs during sleep, and is not affected by antitussive drugs. Physical and radiographic examinations of the respiratory tract and microbiological investigations are normal. Bronchial asthma manifested as chronic cough should be excluded in each patient by lung function testing.